The influence of organizational culture and work motivation toward employee performance (case study on employees of pt inoac polytechno indonesia) - MN, Nuryasman; Suryaman, Eka Andana (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
The purpose of this research is to know how big influence of organizational culture variable and work motivation to employee performance, PT. InoacPolytechno Indonesia, PasarKemis, Tangerang.The method used is quantitative method and analyze the relationship between independent variables with dependent variable, measurement method used is using Likert scale by taking 30 respondents from existing population as research sample. For regression test the researcher uses statistical analysis with smartPLS program3.2.6.From the result of research known equation KK = 0.547 (BO) + 0.292 (MK). Organizational culture has a positive and significant impact on employee performance, which has the ability of p-values 0.000 <0,05. While work motivation has positive and insignificant effect on employee's performance, that is having ability of pvalues value 0,092> 0,05.